THE STUDY OF OXYGEN VACANCY DIFFUSION IN LINIO2-BASED CATHODE MATERIALS - Muhammad Khalfani, Erlant
The utilization of lithium nickel oxide (LNO) as a high-capacity Li-ion battery cathode material is impeded by its low thermal stability. Oxygen evolution occurs spontaneously at higher temperatures, producing an oxygen vacancy site. If the reaction continues, the vacancy sites will diffuse and condense towards a certain planar direction. This condensation of vacancies forms a cracking, which can lead to capacity fading in the material. This research provides a study regarding the mechanisms and paths of oxygen vacancy diffusion in the LNO bulk, comprising of the thermodynamics and kinetics analysis of oxygen vacancy diffusion. Electronic structure analysis is performed to provide further explanation on the mechanisms of oxygen vacancy formation and diffusion. This research is carried out using a material computation method based on Density Functional Theory (DFT), as executed on the software VASP. The aim of this research is to study the formation and diffusion of oxygen vacancy in LNO-based cathode materials. In this study, it is discovered that in Li-excess materials, which contain a Li anti-site defect, unstable configurations emerge which promote the formation of oxygen vacancy. It also reduces the diffusion rate of oxygen vacancy without altering the directional preference. This research may provide guidance in increasing the stability of the LNO-based cathode material.